New anaxyelids (Hymenoptera: Anaxyelidae) from the Cretaceous of Asia - Kopylov, Dmitry S. (Zootaxa, 2019)
Four new genera and five new species of anaxyelids are described from the Cretaceous of Asia: Mangus magnus gen. et sp. nov. from the Aptian of Mongolia (Bon-Tsagan), Urosyntexis undosa sp. nov., Parasyntexis khasurtensis gen. et sp. nov., both from the Early Cretaceous of Transbaikalia (Khasurty), Dolichosyntexis transbaikalicus gen. et sp. nov. from the Hauterivian–Barremian of Transbaikalia (Baissa), and Curiosyntexis magadanicus gen. et sp. nov. from the mid-Upper Cretaceous of NE Siberia (Obeshchayushchiy). Early Cretaceous is the time of the highest diversity of Anaxyelidae. In this epoch these sawflies are represented with all four subfamilies comprising the group. In Late Cretaceous anaxyelid diversity and abundance rapidly decrease and they are represented with the only subfamily Syntexinae. The anaxyelid collection of Palaeontological Institute (Moscow), the most representative collection of fossil anaxyelids in the world, has been completely revised, identified and described. The list of identifications is provided.